Does The Consumption of Energy, Renewable Energy, Natural Resources and Emissions Affect Gross Domestic Product?: The Study of Southeast Asia - Firmansyah, Muhamad Ferdy; Rusliana, Nanang; Komaludin, Ade (Jurnal Wilayah dan Lingkungan, 2024)
We face the challenges of economic growth productivity which still uses dirty energy and minimal efforts to cleaner energy transition. The debate on efforts to increase productivity by diverting dirty energy into clean energy while still preserving nature has long been discused. Southeast Asia is a region that has massive development potential with valuable natural resources facing regional threats in addition to decreasing environmental quality but also prosperity. This study aims to identify initial steps are needed to control energy consumption, which is still considered dirty, the extent of the scope of Southeast Asia's current clean energy transition and how emissions can be a determinant of the decline in regional economic produtivity. This is the first study to combine the Cobb-Douglass production function model with three models that focus on (1) energy consumption, (2) renewable energy and natural resources, and (3) emissions. The data used is secondary data for the period 2004-2018 sourced from the World Bank Development Indicator and ourworlddata.org. Panel data regression was used as an analytical technique. This study was conducted in the Southeast Asia region (with selected countries with developing economies and insutries, namely Indonesia, Malaysia, Thailand, the Philippines and Vietnam). The results of this study show that in the energy consumption model, only labor has a significant effect on GDP, in model B there is renewable energy consumption and the labor force which significantly affects GDP and in model C there are CO2 emissions and GHC emissions that affect GDP in the Southeast Asia region. This research will provide input to policy makers and growth analysts to form policies for sustainable economic development in Southeast Asia.